PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP KESEJAHTERAAN MENTAL REMAJA DI ERA DIGITAL - Nisa Ayu Rahmawati; Anandha Putri Rahimsyah; Dewang Sulistiana (JIEGC Journal of Islamic Education Guidance and Counselling, 2026)
This study aims to determine the effect of social media use on mental well-being in the digital era. This research used a quantitative approach with a correlational design. The participants were 269 students of SMA Negeri 3 Tasikmalaya selected through a simple random sampling technique. Data were collected using social media use and mental well-being instruments. The data were analyzed using descriptive analysis and simple linear regression analysis to examine the effect between variables. The results showed that social media use has an influence on adolescent mental well-being. Most students showed a moderate level of social media use, indicating that social media has become an important part of adolescents’ daily activities. The findings indicate that social media involvement is related to students’ psychological conditions, including emotional and psychological well-being. This study concludes that social media use is one of the factors associated with adolescent mental well-being in the digital era. The results are expected to provide insight for guidance and counseling services in supporting healthy digital behavior among students.